The role of microglia and macrophages in glioma maintenance and progression - Hambardzumyan, Dolores (Nat Neurosci, 2016)
There is a growing recognition that gliomas are complex tumors composed of neoplastic and non-neoplastic cells, which each individually contribute to cancer formation, progression and response to treatment. The majority of the non-neoplastic cells are tumor-associated macrophages (TAMs), either of peripheral origin or representing brain-intrinsic microglia, that create a supportive stroma for neoplastic cell expansion and invasion. TAMs are recruited to the glioma environment, have immune functions, and can release a wide array of growth factors and cytokines in response to those factors produced by cancer cells. In this manner, TAMs facilitate tumor proliferation, survival and migration. Through such iterative interactions, a unique tumor ecosystem is established, which offers new opportunities for therapeutic targeting.